Crop biotechnology update 2: second generation traits and legislation - Halford, Nigel G. (Henry Stewart Talks, 2019)
2nd generation traits in GM crops, High value oils, virus resistance, drought tolerance and golden rice as examples, Regulations on GM crops in the EU, Global regulations on GM crops, Resistance to GM crops approval, The ECJ ruling on GM crops